2021
DOI: 10.1021/jasms.1c00078
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Mass Spectra of Environmental Pollutants Using Computational Chemistry: A Case Study and Critical Evaluation

Abstract: Organic pollutants can be identified by comparing their electron ionization (EI) mass spectra with those in libraries or obtained from authentic standards. Nevertheless, libraries are incomplete; standards may be unavailable or too costly, or their synthesis may be too time-consuming. This study evaluates the performance of quantum chemical electron ionization mass spectrometry (QCEIMS) vis-à-vis competitive fragmentation modeling (CFM) for suspect screening and unknown identification. EI mass spectra of 35 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…It was shown that the program is able to identify semiochemicals and metabolites of prior unknown compounds better than the commonly used CFM-ID program. 30,31 As an alternative to EI, the ionization of molecules can be obtained through protonation. Since the nature of the primary ions between these approaches differs (usually an open-shell vs closed-shell electronic structure), the underlying potential energy surfaces (PESs) are (at least initially) different as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the program is able to identify semiochemicals and metabolites of prior unknown compounds better than the commonly used CFM-ID program. 30,31 As an alternative to EI, the ionization of molecules can be obtained through protonation. Since the nature of the primary ions between these approaches differs (usually an open-shell vs closed-shell electronic structure), the underlying potential energy surfaces (PESs) are (at least initially) different as well.…”
Section: Introductionmentioning
confidence: 99%
“…The program provides reasonable EI mass spectra for organic, inorganic, and transition-metal-containing molecules that agree well with experimental spectra. Because the method is based on MD simulations, the resulting trajectories provide detailed insights into fragmentation processes and rearrangement reactions that are difficult to derive otherwise. It was shown that the program is able to identify semiochemicals and metabolites of prior unknown compounds better than the commonly used CFM-ID program. , …”
Section: Introductionmentioning
confidence: 99%
“…For the discovery of unknown unknowns where no libraries or standards exist, the in-silico prediction of EI spectra (Allen et al, 2016;Spackman et al, 2018;Wang et al, 2020;Wei et al, 2019) is more straight forward than collision-induced dissociation (CID) (Koopman and Grimme, 2021) and higher energy C-trap dissociation (HCD) spectra used for LC-HRMS analysis. Although, it is important to recognize that false positive rates vary across all in silico approaches (Schreckenbach et al, 2021). In addition to predicted spectral matching, EI spectra can be used for molecular networks and substructure characterization (e.g., (Elie et al, 2019;Hummel et al, 2010;Lai et al, 2018;Stein, 1995)).…”
Section: S12 Alternative Ei Spectral Libraries and Ionization Methods...mentioning
confidence: 99%
“…CSI: Finger ID was used by Larson et al to identify products of lignin pyrolysis [42]. QCEIMS was evaluated by Schreckenbach et al [110] to predict the mass spectra of selected halogenated and organophosphorus flame retardants. While QCEIMS is designed for EI spectral prediction, it can also be informative when predicting the CID mass spectra of ions M •+ generated by charge exchange (GC-APCI) or photoionization (GC-APPI).…”
Section: Computational Tools To Predict Mass Spectramentioning
confidence: 99%